Notaris Law Protection Under The Civil Law In Law Number 2 Year 2014 Concerning Amendment To Law Number 30 Year 2004 Regarding Notary Position - Farah Farah; Dewi Sukmaningsih; Gunarto Gunarto (Jurnal Akta, 2018)
Legal protection should be provided to all persons, including Notaries. Legal protection of a Notary can be done through a process, namely: the use of the rights or obligations of non-compliance of Notaries and the calling of a Notary by the investigator, public prosecutor and judge shall be done by obtaining Notary Honorary Council (MKN) approval.The purpose of the research was to analyze the implementation of legal protection to the notary and to know the obstacles as well as the solution in Law number 2 year 2014 on the amendment of Law No. 30 year 2004.This study used a juridical-normative approach obtained from primary data and secondary data analysis techniques and used qualitative data analysis.The results of the study indicated that the legal forms of legal protection to the Notary under the UUJN Law are: 1 Regulation on the obligation of non-disclosure and right of non-disclosure (Article 4 paragraph 2 and Article 16 paragraph 1), 2) Fingerprint attachment in minuta deed (Article 16 paragraph (1) c), 3) Approval of the Notary Public Honor Council (Article 66 paragraph 1), 4) Protection of Indonesian Notary Association (Article 67 paragraph) 5) The obstacle is the absence of change of the Implementing Law of UUJN, the absence of Notary Honorary Council, and the lack of socialization. Legal protection for a Notary to the deeds he made regarding the accountability of a civil notary is the existence of an independent Notary Publicity Council. The government should provide special training to the notary to minimize adverse effects.Keywords: Notary, Legal Protection, UUJN